Tumor-Derived Extracellular Vesicles and the Immune System—Lessons From Immune-Competent Mouse-Tumor Models - Marvin Droste; Marvin Droste; Basant K. Thakur; Brian P. Eliceiri (Frontiers in Immunology, 2020)
Tumor-derived extracellular vesicles (TEVs) are important regulators of the immune response in cancer; however, most research so far has been carried out using cell culture systems. Immune-competent murine tumor models currently provide the best platform to assess proposed roles of TEVs using in vivo animal models and therefore are important for examining interactions between TEVs and the immune system. In this review, we present the current knowledge on TEVs using in vivo tumor-bearing animal models, with a focus on the role of TEVs in mediating crosstalk between tumor cells and both adaptive and innate immune cells. In particular, we address the question how animal models can clarify the reported heterogeneity of TEV effects in both anti-tumor responses and evasion of immune surveillance. The potential of TEVs in mediating direct antigen-presenting functions supports their potential as cancer vaccine therapeutics, therefore, we provide an overview of key findings of TEV trials that have the potential as novel immunotherapies, and shed light on challenges in the path toward the first in-human trials. We also highlight the important updates on the methods that continue to enhance the rigor and reproducibility of EV studies, particularly in functional animal models.